The legacy of civil war: The case of Mozambique - Lena Giesbert; Kati Schindler (Weekly Report, 2011)
How do households cope with post-war economic reconstruction? Are groups of households trapped in poverty? These questions are discussed using the case of Mozambique, a nation in Southern Africa. Shortly after gaining independence in 1975, Mozambique delved into a civil war that lasted until 1992. Our analysis explores poverty dynamics among rural households a decade after the civil war ended. Findings indicate that both income and asset endowments are very low and the prevalence of poverty is high. However, there is no evidence that households are trapped in poverty. Instead, the rural farm-based economy as such provides very few prospects for improved livelihoods. This appears to be one of the legacies of the civil war, which destroyed much of the public infrastructure and the physical asset endowments of households and increased the welfare gap between urban and rural.
Keywords: J12; J22; O12; 330; asset-based approach; Mozambique; poverty trap; shocks; violent conflict